Standardization and optimization of an automotive components production line - Antoniolli, I (2020)
Supported by the concepts and definitions of Standard Work methodology, which underpins Lean Thinking philosophy and Kaizen, the study described in this article was developed at a company in the automotive sector, more specifically directed at a production line manufacturing components for air-conditioning systems. The main objectives were to standardize operations, decrease or eliminate the number of activities those are not generating added-value, enhance productivity and associate continuous improvement actions to the processes at hand in order to eliminate waste. After the implementation of a few simple changes - the standardization of operations, adjustments and allocations of workstations – one was able to tailor the production objectives and cycle times to the line’s capacity. The productivity and efficiency of both machines and workers was also increased. Due to the elimination of waste and generation of value, from the customer’s perspective, one was able to raise the OEE (Overall Equipment Effectiveness) general average by 16%, from 70% to 86%.